دراسة تأثير بعض الركائز على إشارة الامتصاص الذري لعنصر الكادميوم (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تضمنت هذه الدراسة تأثير بعض الأوساط (HNO3 , HCl , H2SO4 , NaCl , NaF) على إشارة الامتصاص الذري لعنصر الكادميوم، وذلك بدراسة تأثير هذه الأوساط على المنحنيات الحرارية للكادميوم، ودراسة تأثير سلسلة من التراكيز لهذه الأوساط على إشارة الامتصاص الذري. استخدم الأنبوب المطلي والأنبوب ذو الصفيحة مع مصحح الديتريوم، كما استخدم كلا الأنبوبين مع مصحح العكس الذاتي (Self-Reversal Corrector) SR عند دراسة تأثير وسطي NaCl , NaF على إشارة الامتصاص الذري لنزر عنصر الكادميوم. تبين وجود تأثير واضح للركازة على سرعة تطاير وتذرير عنصر الكادميوم، كما لحظ ارتباط إشارة الامتصاصية اللانوعية بنوع الركازة المرافقة، ففي حين انعدمت الامتصاصية اللانوعية في التراكيز العالية من HNO3 , HCl ، لحظ ظهورها الواضح في التراكيز العالية من H2SO4 وفي التراكيز المنخفضة من        NaCl , NaF ، ويعود سبب ذلك إلى تطاير الركازة في مرحلة التذرير، يرافقه تشويش قد يفوق قدرة المصحح المستخدم. أظهر مصحح الـSR قدرة على التصحيح تفوق قدرة مصحح الديتريوم عند استخدامه مع الأنبوب المطلي والأنبوب ذي الصفيحة، ولكنَّ حساسية التحليل باستخدام مصحح الـSR أخفض ( حوالي 50% ) من حساسية التحليل باستخدام مصحح الديتريوم. The effect of some matrixes (HNO3, HCl, H2SO4, NaCl, NaF) on the atomic absorption signal of cadmium element was studied. This was obtained by studying the effect of matrixes on the thermal programs of cadmium element, and the effect of series concentrations of these matrixes on atomic absorption signal. A coated tube and platform tube with deuterium corrector, in addition to SR corrector (Self-Reversal Corrector) for NaCl and NaF only, were used. There are clear effects of the presence matrix on the evaporation and atomization of cadmium; whereas, we do not observe any non-specific absorption signals in the presence of high concentration of HCl and HNO3, which appear clearly at high concentrations of H2SO4 and in low concentrations of NaCl and NaF. This interference is due to the volatilization of matrix in the atomization step, accompanied with noise higher than ability of the using corrector. Otherwise, the ability of SR corrector is higher than the ability of deuterium corrector with both coated tube and platform tube, but the analytical sensitivity using SR corrector is lower (about 50%) than the analytical sensitivity using deuterium corrector.